State-building in Kazakhstan continuity and transformation of informal institutions - Sharipova, Dina (Contemporary Central Asia : societies, politics, and cultures, 2018)
"This study examines informal institutions of reciprocity and their connections to state-building in Kazakhstan. The author analyzes both how these institutions changed over time and how they bridged the transition from the Soviet to post-Soviet periods"--